Efeitos da radiação ionizante pós-cirúrgica no reparo ósseo e na osseointegração de implantes: análises microtomográfica, histomorfométrica, biomecânica e de sobrevida - Pitorro, Tássio Edno Atanásio (2013)
Radiotherapy (RT) is one of the strategies used for to treat cancer, which may be associated with surgery and chemotherapy. Despite its efficiency, deleterious effects have been reported in the literature. Part of these effects negatively interfere with the bone metabolism, which may affect bone repair, osseointegration and the survival of dental implants. One of the methodologies used to assess these effects is micro-computed tomography (micro-CT) which, despite having been extensively studied, some issues remain to be clarified. Before be submitted to RT, patients with head and neck cancer undergo an oral screening where oral foci are detected and eliminated, usually culminating in teeth extraction, with the need to rehabilitate these patients in order to restore masticatory function and improve their quality of life. Traditionally, implant placement is performed after RT, alternatively it can be performed previous. In this context, 3 specific objectives were defined for the present study: Specific objective 1: Systematically evaluate the survival rate of dental implants installed pre- and post- radiotherapy. The study demonstrated that implants installed pre- and post-radiotherapy had high survival rates, similar to those of implants installed without associated RT; Specific objective 2: to evaluate the difference between the manual and pre-defined methods for defining the region of interest during the analysis of bone defects using micro-CT and to evaluate the repair process of the bone submitted to radiotherapy after surgery. This study proved that, despite the manual method be time consuming compared to the predefined one, the results provided by this method reflected a more advanced repair process, with no significant difference in repair between irradiated and non- irradiated bone. Specific objective 3: to evaluate the influence of ionizing radiation on the osseointegration of titanium implants installed prior to radiotherapy in rats. The results showed that the influence of RT on the osseointegration of implants installed prior to radiotherapy was not significant.